A US/India Model for China’s Ethnic Policies: Is the Cure Worse than the Disease? - Sautman, Barry (2014)
Some scholars in China argue that minority rights inscribed in law, such as ethnic regional autonomy and preferential policies, must be reformed along liberal lines: minorities should be “depoliticized” -- treated as cultural groups whose members have only individual, not collective, rights. They propose a “second generation of ethnic policies” for China that they argue would resemble policies in the United States and India. This article shows, however, that the United States and India do not have the features of ethnic equity and peace that they are supposed to exemplify, as their minorities have subordinate, deteriorating social positions and are generally disaffected. The choice for China’s minorities need not be a binary of individual rights only or no change in the present system. An expansion, rather than contraction, of minority rights may instead create greater ethnic equality and stability in China